Atlas for living. (Singapore : Page One Publishing, 2008)
This atlas brings together interior design projects by designers and architects from around the world, including Philippe Starck, India Madhavi, Karim Rashid, Matali Crasset, Massimiliano Fuksas and Claudio Silvestrin, the ministry of Design, and many more, in which the reader will find the key points in contemporary trends.
Introduction.--Eclectic.--Industrial.--Minimalism.--Vintage.--Neo Classical.--Neo Modern.--Directory.
Keywords: INTERIOR ARCHITECTURE; INTERIOR DECORATION